May Non-antipsychotic Drugs Improve Cognition of Schizophrenia Patients? - Buoli, M.; Altamura, A. C. (Pharmacopsychiatry, 2015)
Rationale: Cognitive impairment in schizophrenia patients is associated with poor outcome and it represents one of main challenges of pharmacological treatment. Unfortunately, second-generation antipsychotics have not yielded the expected results in the improvement of these symptoms.Objective: The purpose of the present review paper is to summarize and discuss the available data about the efficacy of non-antipsychotic drugs in the treatment of cognitive symptoms of schizophrenia.Methods: A research in the main database sources has been performed to obtain a comprehensive overview. Studies with different methodologies (open and double-blinded) have been included, while studies with schizoaffective patients have been excluded.Results: Several non-antipsychotic compounds have been tested with the purpose to improve cognitive symptoms in schizophrenia patients, but no molecule has a significant pro-cognitive activity.Conclusion: Available data do not support the superiority of non-antipsychotic drugs vs. placebo for cognitive enhancement in schizophrenia. Preliminary results indicate mirtazapine, mianserine, lamotrigine, tandospirone, cyproheptadine, valacyclovir and omega-3 fatty acids as the most promising compounds, however no definitive conclusions can be drawn in the light of small sample size studies.
Keywords: schizophrenia; cognition; psychopharmacology